Tell me if there is a problem: safety in early general practice training. Issue 4 (4th July 2019) - Ingham, Gerard; Plastow, Kayty; Kippen, Rebecca; White, Nicky
ABSTRACT: In contrast to other comparable countries, trainees commencing general practice in Australia can see patients without being required to contact their supervisor. To understand how patient safety in early training is managed a qualitative study design using semi-structured interviews was used. A lead medical educator from each of the nine Australian Regional Training Organisations (RTOs) was interviewed. Transcriptions of interviews were analysed to identify themes. RTOs do not mandate a period of direct observation of trainees and the use of safety checklists for supervision is variable and not monitored. The oversight of training practices by RTOs mirrors that of trainees by supervisors. The onus falls on those being supervised to identify the need for assistance. Despite this, lead medical educators still consider the commencement of general practice training to be safe. Other factors found potentially to impact on safety include the variability of training practices and supervision; the complex RTO-practice relationship; quota-driven selection of doctors into general practice; and the negative impact on education of the funding model. Patient safety may be improved by a period of direct observation of potential trainees prior to the commencement of general practice training and the use of checklists to encourage supervision of high risk activities.